Investigation of Mechanical Properties of Hot Mix Asphalt Modified with Elvaloy and Polyphosphoric Acid - Yilmaz, Mehmet; Yalcin, Beyza Furtana (Avestia Publishing, 2025)
In order for the bituminous hot mix layers to resist the increased traffic load and volume as well as the adverse environmental conditions for a long time without being deformed, the bituminous binder used in the mixture has been commonly modified with the Styrene-Butadiene-Styrene (SBS) polymer. The high demand for SBS makes it difficult to supply and therefore brings on the use of alternative additives. In this study, the combined use of Elvaloy and phosphoric acid (PPA) was investigated. Additionally, the effects on the mechanical properties of bituminous mixtures were examined. Modified binders were prepared using Elvaloy/PPA additives mixed under specified conditions. Hot mix asphalt (HMA) samples prepared with these binders were subjected to Marshall stability and flow, indirect tensile stiffness modulus, and indirect tensile fatigue tests to comprehensively evaluate the effects of modified bi nders on the mechanical properties of bituminous hot mixtures. As a result, the bituminous hot mix tests revealed that asphalt mixtures improved their mechanical properties at the specified ratios. © 2025 Avestia Publishing. All rights reserved.
10th World Congress on Civil, Structural, and Environmental Engineering, CSEE 2025 -- 10 April 2025 through 12 April 2025 -- Barcelona -- 330019
Keywords: Elvaloy; HMA; Mechanical Properties; Modification; PPA